Late Protein Synthesis-Dependent Phases in CTA Long-Term Memory: BDNF Requirement - Martínez-Moreno, Araceli; Rodríguez-Durán, Luis F.; Escobar, Martha L. (Frontiers in Behavioral Neuroscience, 2011)
It has been proposed that long-term memory persistence requires a late protein synthesis-dependent phase, even many hours after memory acquisition. Brain-derived neurotrophic factor (BDNF) is an essential protein synthesis product that has emerged as one of the most potent molecular mediators for long-term synaptic plasticity. Studies in the rat hippocampus have been shown that BDNF is capable to rescue the late-phase of long-term potentiation as well as the hippocampus-related long-term memory when protein synthesis was inhibited. Our previous studies on the insular cortex (IC), a region of the temporal cortex implicated in the acquisition and storage of conditioned taste aversion (CTA), have demonstrated that intracortical delivery of BDNF reverses the deficit in CTA memory caused by the inhibition of IC protein synthesis due to anisomycin administration during early acquisition. In this work, we first analyze whether CTA memory storage is protein synthesis dependent in different time-windows. We observed that CTA memory become sensible to protein synthesis inhibition 5 and 7 hours after acquisition. Then, we explore the effect of BDNF delivery (2 μg/2 μl per side) in the IC during those late protein synthesis-dependent phases. Our results show that BDNF reverses the CTA memory deficit produced by protein synthesis inhibition in both phases. These findings support the notion that recurrent rounds of consolidation-like events take place in the neocortex for maintenance of CTA memory trace and that BDNF is an essential component of these processes.